Physics Learning Innovation: Song and Animation-Based Media as a Learning Solution for Mirrors and Lenses for Junior High School Students - Zakiyah, Zakiyah; Boonma , Kantida; Collado, Resty (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to develop and assess the effectiveness of a physics learning media based on songs and animations to enhance motivation and understanding among Grade VIII students on the topics of mirrors and lenses.. Methodology: The study employed a mixed-methods approach, utilizing a procedural development model by Borg and Gall. Tools and software used include Adobe Audition 1.5, Wondershare Filmora, and Adobe Flash CS6. Data collection methods included questionnaires and expert reviews. Main Findings: The song and animation-based learning media received a